Installing and setting up the Pandas library - Lerner, Reuven 1970- (O'Reilly Media, Inc., 2024)
Python is a popular programming language, and is just getting more popular as time goes on. When we offer courses on O'Reilly's learning platform, one of the biggest issues is that people without a background in programming and computers struggle to install Python, let alone such tools as Jupyter. We have found some fixes, such as recommending Google Colab, but they are insufficient. This video collection will help newcomers to programming to get Python, VSCode, Jupyter, and Pandas installed on their computer. We'll walk them through the installation process, step by step, explaining what is going on, what problems they might encounter, and how to check that things were installed successfully. After following along with these videos' instructions, viewers will have Python, VSCode, Jupyter, and Pandas installed. Moreover, they'll know how to use these tools to write and execute Python code.
Online resource; title from title details screen (O'Reilly, viewed October 28, 2024)
Keywords: Python (Computer program language); Python (Langage de programmation); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet